1971
DOI: 10.1139/y71-016
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the Ionic Composition of the Incubated Artery

Abstract: The ionic composition of the incubated rat tail artery, comparable but not identical to that of the freshly dissected tissue, can be maintained over a period of at least 5 h under aerobic conditions in the absence of utilizable exogenous substrate. A sufficient supply of exogenous glucose must be provided for the maintenance of this ionic composition under anaerobic conditions. The changes in the content of individual ions and water brought about by iodoacetate poisoning can be prevented more or less completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The cellular location of most, if not all, of this change was indicated not only by the constancy of the sum of Na and K, but also by the uniform uptake of Li during the wash at 2°C in both groups; therefore, the sum of monovalent ions was the same in both groups. As usual, the K values in fresh arteries were moderately higher than those in incubated vessels (5,13). An increase in tissue Na and a tendency to a decrease in K were apparent in this experiment.…”
Section: Cellular Na and K In The Tail Artery Of Normal And Hypertenssupporting
confidence: 68%
See 2 more Smart Citations
“…The cellular location of most, if not all, of this change was indicated not only by the constancy of the sum of Na and K, but also by the uniform uptake of Li during the wash at 2°C in both groups; therefore, the sum of monovalent ions was the same in both groups. As usual, the K values in fresh arteries were moderately higher than those in incubated vessels (5,13). An increase in tissue Na and a tendency to a decrease in K were apparent in this experiment.…”
Section: Cellular Na and K In The Tail Artery Of Normal And Hypertenssupporting
confidence: 68%
“…It still must be shown that the value of cellular Na so defined increases in proportion to K loss following conventional Na enrichment of cells by interruption of Na transport (13).…”
Section: Na-exchange In Na-enriched Arteries During LI Substitution Amentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that even if the tissues incubated sequentially are not optimally oxygenated, anaerobic metabolism in vascular tissue is, as reported, quite efficient. 4 It might be urged that the relatively enhanced K + uptake in the SHR in these kinetic experiments simply indicates that these vessels can more effectively recruit energy from glycolysis under the hypoxic conditions of this procedure. Against this, however, is the parallel observation of enhanced K + accumulation in fully aerobically incubated arteries in steady-state.…”
Section: Discussionmentioning
confidence: 97%
“…It may be relevant that our experiments deal with an incubated artery after prolonged incubation, while the Rb-uptake experiments have centered on the freshly excised artery from which the energy stores are presumably depleted. 4 ' 2 " Thus, the mode of activity of the Na pump which depends in large measure on the ADP-ATP ratio may differ in the two procedures. 27 ' M Finally, the Rb-uptake experiments may simply reflect the fact that hypertension exists, since similar results have been reported for both renal and DOCA hypertension.…”
Section: Discussionmentioning
confidence: 99%